Resiliensi Dalam Perspektif Gender di Lingkungan Perguruan Tinggi - Kodariyah, Kodariyah (Fakultas Tarbiyah dan Keguruan, 2024)
In the domains of psychology and education literature, resilience has been recognized as an important pillar in overcoming academic challenges and stress, as well as advancing student well-being. However, there is still a gap in understanding regarding how resilience develops and is presented differently between male and female students. In this context, this research aims to in-depth describe the differences in levels of resilience between male and female students at Indraprasta University PGRI Jakarta. Using a comparative method, this research involved a sample of 175 final year students, consisting of 70 male students and 105 female students, spread across Indraprasta University PGRI Jakarta. Analysis was carried out using the independent sample t-test technique. The research results show that there is a significant difference in the level of resilience between male and female students at Indraprasta University PGRI Jakarta. It was found that the level of resilience in male students tends to be higher than in female students, as reflected in their ability to answer the resilience instruments tested.